Complete Genomic Sequence of European Bat Lyssavirus 1, Isolated from Eptesicus isabellinus in Spain - Marston, Denise A. (Genome Announc, 2015)
All members of the lyssavirus genus cause the disease rabies. European bat lyssavirus 1 (EBLV-1) viruses are divided genetically into three groups according to geographic location and host reservoir. We report here the first genome sequence for an EBLV-1 isolated from Eptesiscus isabellinus in the Iberian Peninsula, Spain.